2022
DOI: 10.1111/avsc.12669
|View full text |Cite
|
Sign up to set email alerts
|

Observer‐driven pseudoturnover in vegetation monitoring is context‐dependent but does not affect ecological inference

Abstract: Aims: Resurveys of vegetation plots are prone to several errors that can result in misleading conclusions. Minimizing such errors and finding alternative approaches for analyzing resurvey data are therefore important. We focused on inter-observer error and excluded other sources of variation. Our main questions were: How large is the inter-observer error (i.e. pseudoturnover) in vegetation surveys, and can it be reduced by simple data aggregation approaches? Which factors are affecting pseudoturnover and does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Studies based on Landolt indicator values can be divided into three groups: studies of the flora of large areas (21% of all articles), studies of various plant communities (68%) (Table 2) and studies of individual plant species (11%). The study of flora was mainly carried out using modern methods and had a methodological character [41][42][43][44]. Over a five-year period, 19 articles were published.…”
Section: Type Of Plant Community Under Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies based on Landolt indicator values can be divided into three groups: studies of the flora of large areas (21% of all articles), studies of various plant communities (68%) (Table 2) and studies of individual plant species (11%). The study of flora was mainly carried out using modern methods and had a methodological character [41][42][43][44]. Over a five-year period, 19 articles were published.…”
Section: Type Of Plant Community Under Researchmentioning
confidence: 99%
“…Moreover, the researchers proposed a novel methodological approach that combines empirical knowledge on the determinants of soil seed bank characteristics with a modern, flexible statistical approach based on machine learning [93]. Interobserver error was analyzed in vegetation monitoring [42]. The main data on the "Database of anthropogenic vegetation of Urals and adjacent territories" registered in the Global Index of Vegetation-Plot Databases and the European Vegetation Archive are presented [24].…”
Section: Characterization Of Research Topicsmentioning
confidence: 99%
“…The resurvey was supervised by the original surveyor (M. Chytrý) to limit the observer-driven pseudoturnover (Boch et al, 2022). It was conducted between 4 June and 16 August.…”
Section: Vegetation Survey and Resurveymentioning
confidence: 99%
“…However, total species richness is not necessarily a suitable indicator to re ect environmental changes, as values mainly peak under environmental conditions with intermediate productivity and disturbance (Grime 1973;Huston 2014;Bergauer et al 2022). In addition, temporal patterns in species richness may be biased, as such measures are prone to observer differences (Archaux et al 2009;Burg et al 2015), and it has been shown that species lists of vegetation plots that were compiled by different observers usually differ from each other to a certain degree (Kapfer et al 2017;Boch et al 2022). Further, it has been shown that prior experience and training in conducting vegetation surveys can particularly affect species numbers (because of a greater ability to detect and identify species) and cover estimates over time (reviewed by Morrison 2016).…”
Section: Introductionmentioning
confidence: 99%